Whipple Disease Presenting as Isolated Transverse Myelitis with Permanent Neurological Damage in a Patient with Systemic Lupus Erythematosus: A Case Report of a Difficult Diagnosis with a Literature Review - Carolina Saffioti; Marta Nebiolo; Roberta Caorsi; Alessio Mesini; Mariasavina Severino; Giacomo Brisca; Elio Castagnola; Marco Gattorno (MDPI AG, 2024)
We describe an atypical case of Whipple disease exclusively involving the spinal cord in an adolescent receiving immunosuppressive therapy for systemic lupus erythematosus. The diagnosis was particularly difficult since lupus and Whipple disease can present similar clinical features and the patient's prolonged contact with sewage was initially not mentioned. A literature review of the clinical, imaging, diagnostic, and therapeutic challenges of Whipple disease is also performed.